Ambivalensi Penggunaan Video Animasi dalam Pembelajaran SKI: Dampak terhadap Motivasi dan Konsentrasi Belajar Siswa MAN 2 Bireuen - Muksalmina Muksalmina; Daysra Abrar; zubaidah zubaidah (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2025)
This study aims to examine the ambivalence of using animated videos in learning Islamic Cultural History (SKI) at MAN 2 Bireuen, especially its impact on students' motivation and concentration in learning. This study uses a qualitative approach with the classroom action research (CAR) method for grade XI students. The results show that animated videos can increase learning motivation, but also have the potential to decrease concentration due to visual distraction. This study concludes that the effectiveness of animated videos is highly dependent on how teachers implement them, and there needs to be a pedagogical strategy to maximize their impact.